2020
DOI: 10.1007/s10548-020-00758-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Frequency-Dependent Brain Networks from Ongoing EEG Using Spatial ICA During Music Listening

Abstract: Recently, exploring brain activity based on functional networks during naturalistic stimuli especially music and video represents an attractive challenge because of the low signal-to-noise ratio in collected brain data. Although most efforts focusing on exploring the listening brain have been made through functional magnetic resonance imaging (fMRI), sensor-level electro-or magnetoencephalography (EEG/MEG) technique, little is known about how neural rhythms are involved in the brain network activity under natu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
(71 reference statements)
2
9
0
Order By: Relevance
“…Thus, the forming of these connectivity patterns is plausible to understand semantics expressed by music and induce related emotion during music listening. For the neural oscillations, previous studies reported that cortical rhythm activity in the Beta range is related to behavioral performance during music listening and associated with predicting the upcoming note events [12], [60], which confirms our results that the frontal high-order networks with a high coherence in the Beta range emerged during music listening. In addition, the Delta-specific high-order cognitive network (Row I of Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the forming of these connectivity patterns is plausible to understand semantics expressed by music and induce related emotion during music listening. For the neural oscillations, previous studies reported that cortical rhythm activity in the Beta range is related to behavioral performance during music listening and associated with predicting the upcoming note events [12], [60], which confirms our results that the frontal high-order networks with a high coherence in the Beta range emerged during music listening. In addition, the Delta-specific high-order cognitive network (Row I of Fig.…”
Section: Discussionsupporting
confidence: 91%
“…These networks involved in auditory areas ( Fig. 4) showed beta-specific modes, which play an important function in music perception in agreement with previous studies [12], [17], [60].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, the multi-mode data were stacked or concatenated to facilitate two-way processing methods (e.g., independent component analysis (ICA) and principal component analysis (PCA)) for extracting interested brain activities (Bernat et al 2005;Cong et al 2010;Dien 2010;Tenke and Kayser 2005;Vigário and Oja 2008;Zhu et al 2020b). The procedures of stacking and concatenating inevitably lost potential interaction information (Cong et al 2015(Cong et al 2013a.…”
Section: Tensor Component Analysismentioning
confidence: 99%
“…Considering the temporal and spectral dynamics of spatial couplings (e.g., functional connectivity) for multiple participants in a cognitive task, a multi-way dataset structure is naturally formed. This multi-dimensional nature points to the adoption of tensor decomposition models instead of matrix decomposition models which normally fold some dimensions and ignore the hidden interactions across different modes [23], [25]- [28]. Canonical Polyadic (CP) decomposition is derived in terms of the sum of multiple rank-one tensors, and each rank-one tensor represents the covariation of the corresponding components from each mode [29], [30].…”
Section: Introductionmentioning
confidence: 99%